2022
DOI: 10.3390/pharmaceutics14112457
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Applications of Green Synthesized Bimetallic Nanoparticles from Ocimum basilicum

Abstract: Antibiotic resistance is an important and emerging alarm for public health that requires development of new potential antibacterial strategies. In recent years, nanoscale materials have emerged as an alternative way to fight pathogens. Many researchers have shown great interest in nanoparticles (NPs) using noble metals, such as silver, gold, and platinum, even though numerous nanomaterials have shown toxicity. To overcome the problem of toxicity, nanotechnology merged with green chemistry to synthesize nature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Figure 2 indicates the biosynthesis peaked after three hours. The findings of our research utilizing UV-Vis spectroscopy are in accordance with those of an earlier study that used a variety of plant extracts [46][47][48].…”
Section: Uv-vis Spectrophotometrysupporting
confidence: 90%
“…Figure 2 indicates the biosynthesis peaked after three hours. The findings of our research utilizing UV-Vis spectroscopy are in accordance with those of an earlier study that used a variety of plant extracts [46][47][48].…”
Section: Uv-vis Spectrophotometrysupporting
confidence: 90%
“…Silver and platinum nanoparticles were synthesized from O. basilicum L. leaf extracts by green synthesis method and their antibacterial activity was investigated by using them separately and in combination. The MIC value for the AgNPs was determined as 3.12 µg mL -1 and 6.25 µg mL -1 for gram positive and negative bacteria, respectively [24]. The antibacterial effect of AgNPs which is formed by combining O. basilicum and Hibiscus sabdariffa L. plant extracts were investigated, and the MIC value was determined as 6.25 µg mL -1 [26].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 The SEM images of synthesized AgNP Malapermal et al, (2017) [23], More et al (2022)[24] were reported that synthesized AgNPs by Ocimum species were found to be crystalline and relatively spherical Melkamu et al (2022) [25]. reported that as a result of SEM analysis of Ocimum sanctum-AgNP had a various sizes including spherical, cubic and flake-shaped (20 nm).…”
mentioning
confidence: 99%
“…41−43 However, literature indicates that on increasing leaf extract concentration and AgNO 3 mM concentration beyond a certain level, the rate of Ag NP formation decreases. 44,45 It is also found that on increasing the reaction time and temperature, Ag NP synthesis rate increases. 44,45 2.4.…”
Section: Synthesis Of Silver Npsmentioning
confidence: 93%